A prospective quality improvement initiative in adult hemophagocytic lymphohistiocytosis to improve testing and a framework to facilitate trigger identification and mitigate hemorrhage from retrospective analysis. Issue 31 (August 2018) - Merrill, Samuel A.; Naik, Rakhi; Streiff, Michael B.; Shanbhag, Satish; Lanzkron, Sophie; Braunstein, Evan M.; Moliterno, Alison M.; Brodsky, Robert A.
Abstract : Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a highly fatal, hyperinflammatory syndrome in adults triggered by an underlying illness in most cases. As such, suspicion of HLH dictates further investigation to identify the HLH trigger and determine treatment. HLH is clinically challenging due to diverse presentations and underlying triggers, provider unfamiliarity, and bleeding complications. Clinically, we observed diagnostic error from incorrect testing and cognitive biases (interleukin-2 confused with soluble interleukin-2 receptor and natural killer cell quantification confused with functional assays). This study reports our single institutional experience with adult HLH with the aim to reduce erroneous testing with a quality improvement (QI) project, and to facilitate trigger discovery and mitigate hemorrhage. Provider education on HLH testing was the prospective intervention, followed by mistaken test removal. HLH triggers and diagnostic utility were determined by retrospective chart review. Risk factors for hemorrhage were determined by multivariable analysis. Erroneous HLH testing was reduced from 74% to 24% of patients ( P < .001) by the QI intervention. These changes were projected to save 11, 700 yearly. The majority (64%) of patients evaluated for HLH were on non-hematology/oncology services, highlighting the need for vigilance in hematology consultation. Sixty-three patients met classic HLH-2004 criteria for HLH. Malignancy (38%), infection (27%), Epstein–Barr virus (EBV) (14%), or autoimmune disease (8%) triggered most HLH cases. HLH triggers were most commonly identified by serologic testing (27%) and bone marrow biopsy (19%). Biopsy of other affected organs based on PET-CT imaging after unsuccessful initial diagnostic measures was helpful, and focal fluorodeoxyglucose uptake was predictive of an underlying malignancy (likelihood ratio 8.3, P = .004). Major hemorrhage occurred in 41% of patients. On multivariable analysis the odds ratios (OR) for major hemorrhage were increased for patients with intensive care unit level care (OR 10.47, P = .005), and disseminated intravascular coagulation in the first week of admission (OR 10.53, P = .04). These data are incorporated into a framework to encourage early HLH recognition with the HScore, facilitate trigger identification, identify those at risk for hemorrhage, and minimize low-yield or erroneous testing. Abstract : Supplemental Digital Content is available in the text